Placing Immigration, Settlement and Integration in a Canadian City - Dam, Huyen (My University, 2021)
International migration flows and patterns shaped by the determinants, processes and outcomes of social, political, and economic conditions have led to important transformation of society and human geographies. As Canada continues to effectively manage its immigration system and uphold its commitment to international refugee protection and resettlement, it is critical for Canada to do so with an understanding of the changing context of immigration, which are reinforced by shifting policies and their impact, in our contemporary society. In this thesis, the migration trajectory of three groups of newcomers to Canada; international students, Syrian refugees, and refugee youth, are explored by examining policies and conditions that can create group risks and vulnerabilities in immigration, settlement, and integration as groups transition to life in Canada after arrival. As suggested by Castle (2010) migration researchers can advance the field by embedding their work in broader theories of social change to facilitate understanding of the complexity, interconnectedness, variability, contextuality, and multi-mediation of migratory process in the context of rapid change. This thesis employs a geographical lens of place to deepen understanding of processes and outcomes in our contemporary society, while responding to these evolving contexts in one mid-size, post-industrial Canadian city. In three separate research, this thesis examines: 1) economic immigration flow under Express Entry in 2015 and 2016; 2) the role of the voluntary sector during the Syrian Refugee Resettlement Initiative in Hamilton, Ontario in 2016; and 3) the place of school-based settlement in bridging and brokering school-based mental health for newcomer youth.
Keywords: economic immigration; newcomer youth mental health; refugee resettlement; cultural brokering; voluntary sector; structuration theory; international students; place-based policy